"We're all in this together"? Reflections on inequity during tumultuous times. Issue 173 (2nd June 2022) - Hansman, Catherine A.
Abstract: This article discusses the interwoven disruptions caused by the multiple crises of the COVID‐19 pandemic, violent incidents against persons of color, social justice concerns, and political and civil unrest. Discussion will center on how these crises impacted and continue to affect careers, schools, workplaces, and personal lives. The chapter will conclude with frameworks of care that can be adapted by adult learners and educators to respond to ongoing crises.